PUBLIC SPACE DEVELOPMENT DIMENSIONS: A CRITICAL REVIEW - Shukla, Amrita; Chhabra, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Public spaces are integral part of human life since ancient civilization. The traces can be found if form of Greek’s agora, Roman’s forum, Indian ghats etc. For the understanding of this crucial space, the paper presents a comprehensive review of literature relating to components for successful public spaces. The paper intents to understand initiatives adopted around the globe for the development of Public Space by comparing the suggested components and identify the gap in context of developing country with high density such as India. A systematic literature review is conducted to understand the expectations and requirements from public place. The finding highlights that women safety, gender ratio, engagement in and around the public space are yet to be explored. Also, safety cannot be equated with the security as it is a subspace of same. The theory of broken window needs to be mitigated and amalgamated with development of public place, to ensure maximum utilization of public space in developing countries. The study is helpful for constructing/ modifying the public space development toolkit.